INDEKS KECUKUPAN AIR UNTUK PENETAPAN WAKTU BERA KEDELAI DI JAWA TENGAH(WATER SUFFICIENCY INDICES TO DETERMINE FALLOW PERIODS OF SOYBEAN IN CENTRAL JAVA) - Setiapermas M.N.; Yonny Koesmaryono; Yusmin .; Irianto G. (Agromet, 2005)
Climate anomaly has impact on yield and productivity of soybean. An alternative to minimize its impact, it is important to determine period of fallow for soybean in dry land. Period of fallow was determined by using agroclimate analysis such as water satisfaction index (WSI). WSI required daily climate data, soil and agronomy parameter to calculte ETR/ETM fluctuation . Agroecology and soybean yield data were collected from October 2003 to February 2004 in Pondok Village, Ngadirejo Sub-District, Wonogiri District and in Pojok Village, Nogosari Sub-District, Boyolali District . Fallow period was analyzed using CWB-ETo, a daily water balance software developed by IAHRI based on FAO method. WSI was calculated for El-Nino and La-Nina years to determine planting period. The result showed that fallow period were different between locations due to soil and climate variability. The longest fallow period is Blora District from Januri III to October II. While the shortest fallow period are Semarang and Magelang.